Exploring the utility of nursing student‐led health fairs: Educating the college population. Issue 4 (4th February 2022) - Matsuda, Yui; Halstead, Valerie; Falcon, Ashley; Valdes, Beatriz; Salani, Deborah A.; Reaves, Régine P.
Abstract: Objective: The purpose of this study is to examine public health nursing (PHN) students' experiences delivering peer‐to‐peer health education to college students during a health fair. Design: A qualitative, descriptive research design was used. Sample: Senior‐level nursing students ( n  = 13) completing the clinical portion of a PHN course. Measurements: A semi‐structured focus group guide consisting of 10 questions and follow‐up probes was used to elicit PHN student experiences. Focus groups were recorded, transcribed, and analyzed using a thematic analysis technique. Results: Five main themes were identified: (1) benefits of health fairs in general, (2) benefits of nursing‐student‐led health fairs, (3) negatives of nursing‐student‐let health fairs, (4) importance of interaction, and (5) suggestions for maximizing the potential of nursing student‐led health fairs. Conclusions: Although challenges exist, PHN students experienced several benefits from the provision of peer‐to‐peer health education. College campuses represent a unique clinical site that allows nursing students to utilize their insider status to better assess, understand, and provide tailored health education to the college community. This clinical site has shown to provide positive experiences for nursing students and is critical in developing essential nursing skills and building confidence for future clinical rotations.